2020
DOI: 10.1016/j.annonc.2020.08.378
|View full text |Cite
|
Sign up to set email alerts
|

276O Pooled analysis of patient (pt)-reported quality of life (QOL) in the MONALEESA (ML)-2, -3, and -7 trials of ribociclib (RIB) plus endocrine therapy (ET) to treat hormone receptor–positive, HER2-negative (HR+/HER2−) advanced breast cancer (ABC)

Abstract: Conclusions:In pts receiving first-line ET across the ML trials, RIB delayed deterioration in QOL. TTDD for GHS, pain, and emotional functioning scores was longer with RIB vs. PBO. Overall, this large, robust analysis demonstrated favorable QOL results with the addition of RIB to ET in patients with HR+/HER2À ABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…Subsequently, ribociclib and abemaciclib exhibited remarkably similar outcomes when used in combination with endocrine therapy (ET) [ 5 , 6 , 7 , 8 , 9 ]. CDK4/6 inhibitors are oral medications, well-tolerated, and do not negatively impact quality of life [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, ribociclib and abemaciclib exhibited remarkably similar outcomes when used in combination with endocrine therapy (ET) [ 5 , 6 , 7 , 8 , 9 ]. CDK4/6 inhibitors are oral medications, well-tolerated, and do not negatively impact quality of life [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most such analyses revealed combination therapy and endocrine monotherapy were associated with similar quality-of-life scores 45 , 46 , 47 , while one study revealed a benefit for combination therapy 48 . Recently, a pooled analysis of all ribociclib studies was performed 49 . Reviewing all studies, this analysis showed that combination therapy can significantly delay deterioration in quality of life.…”
Section: Treatment Of Patients With Metastatic Breast Cancermentioning
confidence: 99%
“…Reviewing all studies, this analysis showed that combination therapy can significantly delay deterioration in quality of life. In subgroup analyses, which generate hypotheses, the effect was greatest in patients between 45 and 60 years of age and in patients with visceral metastases 49 .…”
Section: Treatment Of Patients With Metastatic Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations